Development of Tourism Villages To Increase Local People'S Income In Tamboke Natural Baths, North Luwu Regency - Pratama, Rival; Mustafa, Sri Wahyuny; Badewi, Muhamad Hadis (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This research aims to explore the potential of the Tamboke Natural Bath, North Luwu Regency, as a tourism village to increase local community income.Methodology: A quantitative approach was applied using purposive sampling on 100 visitors. Data were collected via a Likert-scale questionnaire and analyzed with simple linear regression to measure the effect of tourism village development on community income. Results: Findings reveal that tourism village development has a positive and significant impact, contributing 52.3% to the increase in community income.Findings: Although village fund management meets welfare indicators—educational, economic, and democratic justice—challenges persist, including delayed reporting, suboptimal web-based systems, budget transfers, and limited security programs. The village government is committed to improving governance, emphasizing transparency and equitable resource distribution. Novelty: This study uniquely integrates tourism development analysis with village fund governance evaluation, offering a holistic perspective on how sustainable tourism and financial management can jointly enhance welfare. Originality: The direct link between tourism strategies and fiscal governance in this rural context provides a model for other villages with similar potential. Conclusion: Tourism village development in Tamboke significantly improves community income, underscoring the need for strategic planning, transparent management, and active community participation. Paper type: descriptive quantitative research